Characterization of 2024 T3 Aluminum Alloy after Rare Earth Desmutting. Issue 6 (26th February 2016) - Gordovskaya, I. V.; Curioni, M.; Hashimoto, T.; Walton, J.; Thompson, G. E.; Skeldon, P.
Abstract : The effect of CeCl3 and CeCl3 + H2 O2 additions to a nitric acid solution for desmutting of 2024 T3 aluminum alloy has been investigated using scanning electron microscopy and energy dispersive X-ray analysis, potentiodynamic polarization and X-ray photoelectron spectroscopy. No S-, θ-phase and Al-Cu-Fe-Mn-(Si) particles were detected on the alloy surface after desmutting with added CeCl3 . A similar result was attained with addition of H2 O2, although with slower removal of the particles. In contrast, θ-phase, Al-Cu-Fe-Mn-(Si) and dealloyed S-phase particles remained following desmutting in nitric acid alone. The absence of the particles on the alloy surfaces following desmutting in the presence of CeCl3 was also confirmed by potentiodynamic anodizing of the alloy in H2 SO4 solution.